Peluang Usaha Sebagai Kreativitas Mahasiswa Untuk Berwirausaha - Jamilah Zr; Khairani Munadia; Sandrina As Zahra Lubis; Mansur Keling (BADAN PENERBIT STIEPARI PRESS, 2023)
Business opportunities are the courage to take risks. Business opportunities are not something that come by themselves, but an entrepreneur needs the ability to read opportunities to be able to take action to make these opportunities a reality with creativity and innovation. The aim of this research is to increase student creativity in obtaining business opportunities. The method used is qualitative research and interviews